LOAN-PORTFOLIO QUALITY AND MANAGERIAL EFFICIENCY IN BANKING - DRIGĂ, Imola; DURA, Codruța (Annales Universitatis Apulensis Series Oeconomica; Vol 2 No 17 (2015): Annales Universitatis Apulensis Series Oeconomica, 2015)
As poor management of loans of loans has often been the main cause of bank losses and failures in this area, this paper aims to make a parallel between the quality of loans from bank portfolios and the financial performance of banks. The study is divided into three parts. Thus, the first part refers to trends in the evolution of the quality of loans within EU countries, while the second half continues with an in-depth examination of the situation of non-performing loans in the Romanian banking system. The last part of the paper presents aspects regarding the performance of the Romanian banking system and performs a comparative study on the performance obtained in recent years by leaders of the Romanian banking market.